Heart of yoga revealed - White, Judy L.; Sartwell, Debbie (Ashland, Ohio : Truth Cross Pub., 2010)
The Heart of Yoga Revealed! is a creative nonfiction shocking expose. Most people believe that yoga is just a stretching exercise. This book reveals documented supernatural occult occurrences and personal testimonies from Hindu and Buddhist yoga masters. Yoga masters reveal the obscure occult secrets that have long been concealed. Clearly presented to the reader are the yoga postures containing the Sanskrit alphabet. The alphabet automatically transmits worshipful vibrations in the form of a sign language regardless of the Christians' desire to worship Jesus Christ. The book of Proverbs emphasizes that it is wise for each of us to obtain understanding. I invite you to explore the incredible facade of the yoga phenomenon and to discover how the Lord Jesus Christ by His Holy Spirit reveals the truth about the heart of yoga.
On cover: What every enlightened Christian must know about the dark secrets of Yoga.
Includes bibliographical references.
Description based on print version record.
Keywords: Christianity and yoga; RELIGION / Christian Life / Spiritual Warfare; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books